Gastric ultrasound in the third trimester of pregnancy: a randomised controlled trial to develop a predictive model of volume assessment1. (19th December 2017) - Arzola, C.; Perlas, A.; Siddiqui, N. T.; Downey, K.; Ye, X. Y.; Carvalho, J. C. A.
Summary: Bedside gastric ultrasonography can be performed reliably by anaesthetists to assess gastric content in the peri‐operative period. We aimed to study the relationship between gastric cross‐sectional area, assessed by ultrasound, and volumes of clear fluids ingested by pregnant women. We recruited 60 non‐labouring third‐trimester pregnant women in a randomised controlled and assessor‐blinded study. A standardised scanning protocol of the gastric antrum was performed in the 45° semirecumbent and 45° semirecumbent‐right lateral positions. Subjects were randomly allocated to drink one out of six predetermined volumes of apple juice (0 ml, 50 ml, 100 ml, 200 ml, 300 ml, 400 ml). Qualitative and quantitative assessments at a baseline period after an 8‐h fast, and immediately after the drink, were used to establish the correlation between antral cross‐sectional area and volume ingested. A predictive model to estimate gastric volume was developed. Antral cross‐sectional area in the semirecumbent right lateral position significantly correlated with the ingested volume (Spearman rank correlation = 0.7; p < 0.0001). A cut‐off value of 9.6 cm 2 discriminated ingested volumes ≥ 1.5 ml.kg −1 with a sensitivity of 80%, a specificity of 66.7%, and an area under the curve of 0.82. A linear predictive model was developed for gastric volume based only on antral cross‐sectional area (Volume (ml) = −327.1 + 215.2 × log (cross‐sectional area) (cm 2 )). We conclude that in pregnant women in the third trimester of gestation, the antral cross‐sectional area correlates well with volumes ingested, and this cut‐off value in the semirecumbent right lateral position discriminates high gastric volumes.